2013
DOI: 10.1007/s00064-013-0233-8
|View full text |Cite
|
Sign up to set email alerts
|

Die Korrektur posttraumatischer Deformitäten am Unterschenkel mit dem „Taylor Spatial Frame“

Abstract: The correction of posttraumatic lower leg deformities using the TSF was performed in 6 cases. The mean deformity was 15° (12-22°) in the frontal plane and 6° (4-8°) in the sagittal plane. The correction time was 19 days (14-22 days). The deviation between planned and achieved correction was 0-3° in the frontal plane and 0-2° in the sagittal plane. The osseous consolidation of the osteotomy site was carried out in the TSF in 5 cases with a mean external fixation time of 112 days (94-134 days). In one case, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…La calidad ósea y el estado de las partes blandas son esenciales para el éxito del tratamiento, es importante el procedimiento quirúrgico, pero también lo es el posoperatorio que requiere un seguimiento y la prevención de cualquier dificultad que pueda surgir. [13][14][15] conclusIones El método Ilizarov es excelente para el tratamiento de rescate de las secuelas postraumáticas de la tibia. La planificación minuciosa y el compromiso del paciente han sido factores determinantes en el resultado obtenido.…”
Section: Discussionunclassified
“…La calidad ósea y el estado de las partes blandas son esenciales para el éxito del tratamiento, es importante el procedimiento quirúrgico, pero también lo es el posoperatorio que requiere un seguimiento y la prevención de cualquier dificultad que pueda surgir. [13][14][15] conclusIones El método Ilizarov es excelente para el tratamiento de rescate de las secuelas postraumáticas de la tibia. La planificación minuciosa y el compromiso del paciente han sido factores determinantes en el resultado obtenido.…”
Section: Discussionunclassified
“…Although lots of studies have shown excellent deformity correction of the TSF [10][11][12][13][14][15], there is little published data demonstrating the clinical outcomes of fractures [8,9,16]. As more general orthopedic surgeons are becoming familiar with this versatile device, the TSF is gaining popularity in acute tibial shaft fracture care.…”
Section: Introductionmentioning
confidence: 99%
“…xator that consists of 2 rings or partial rings connected by 6 telescopic struts at special universal joints 1,2 .Considering the advantages of stability, reliability and the versatility of correcting translation, angulation and rotation deformities in the coronal, sagittal and axial planes simultaneously by adjusting the lengths of struts based on the electronic prescription, this system was played an important role over the years in the treatment of bone nonunion, bone fracture and correction of deformity [3][4][5][6][7][8][9] .This kind of hexapod external xator allow the surgeon correct complex multi-planar deformities without the need to alter the frame construct 8,10−12 . Deformity, mounting and frame parameters are needed to enter into a computer-based software when applying the TSF. The deformity and mounting parameters were measured on the basis of the digital radiography according to its instruction.…”
Section: Introductionmentioning
confidence: 99%